Tren Publikasi Penelitian Pendekatan Saintifik dalam Pendidikan: Analisis Bibliometrik Menggunakan VOSviewer - Eklesia Marganingrum; Heny Sri Astutik; Syamsulrizal; Mursalim; Ihsan; Mivtha Citraningrum (Media Pendidikan Matematika, 2026)
This study aims to analyze publication trends related to the scientific approach using bibliometric analysis. The analysis focuses on the development of publication numbers, citation trends, journal sources, productive researchers, and keyword co-occurrence patterns in scientific publications. The data were obtained from the Dimensions database for the period 2020–2025 using the keyword scientific approach. The document selection process followed the PRISMA flow, resulting in 9,861 articles for further analysis using VOSviewer version 1.6.20. The findings indicate that publications on the scientific approach have increased consistently over the years, accompanied by a growing number of citations. The network visualization reveals that scientific approach is associated with ability, but it is not directly connected to mathematics. This finding indicates a research gap in the integration of the scientific approach into mathematics learning oriented toward the development of students’ abilities. Meanwhile, the overlay visualization shows that framework, RBL-STEM, and technology have emerged as recent research trends. The density visualization further indicates that topics such as teacher, knowledge, and class have a high research density, whereas studies linking scientific approach, ability, and mathematics remain relatively limited. Therefore, this study provides a comprehensive overview of the development of scientific approach research and offers opportunities for future studies in the context of mathematics learning based on the scientific approach.